2010
DOI: 10.17221/34/2009-pps
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the effects of insecticidal seed and foliar treatments on pea leaf weevils (Sitona lineatus L.) in the field pea (Pisum sativum L.)

Abstract: Seidenglanz M., Rotrekl J., Smýkalová I., Poslušná J., Kolařík P. (2010): Differences between the effects of insecticidal seed and foliar treatments on pea leaf weevils (Sitona lineatus L.) in the field pea (Pisum sativum L.). Plant Protect. Sci., 46: 19-27.Tested seed treatments (two doses of thiamethoxam, thiamethoxam + fludioxonil + metalaxyl-M; two doses of clothianidin + beta-cyfluthrin) showed high effects on pea leaf weevils (Sitona lineatus L.) which approved relatively long-lasting and sufficient prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…per 100 kg of seed (∼ 82 g. of a.i./ha at the recommended seeding rate of 275 kg/ha as per Government of Saskatchewan Agriculture Knowledge, http://www.agriculture.gov.sk.ca/) had the lowest levels of feeding damage to stipules and was similar to the 50 g dose. These results are similar to those reported by Seidenglanz's et al (2010) field study in the Czech Republic, who found no consistent differences in S. lineatus notching to unfolded pea stipules between a low dose (87.5 g of a.i./ha), equivalent to the registered rate in Canada, and a dose that was two-fold higher. The results of the present study also showed that using a lower rate would not result in a reduction of damage that differed from the untreated plants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…per 100 kg of seed (∼ 82 g. of a.i./ha at the recommended seeding rate of 275 kg/ha as per Government of Saskatchewan Agriculture Knowledge, http://www.agriculture.gov.sk.ca/) had the lowest levels of feeding damage to stipules and was similar to the 50 g dose. These results are similar to those reported by Seidenglanz's et al (2010) field study in the Czech Republic, who found no consistent differences in S. lineatus notching to unfolded pea stipules between a low dose (87.5 g of a.i./ha), equivalent to the registered rate in Canada, and a dose that was two-fold higher. The results of the present study also showed that using a lower rate would not result in a reduction of damage that differed from the untreated plants.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is important because it shows that growers should not need to take control action for early seeded crops when the weevils arrive past the 5 th node. This is the first study to present data on S. lineatus larval mortality in relation to thiamethoxam, which suggests activity of the chemical in the nodules; Seidenglanz et al (2010) also reported an effect on larval mortality but neglected to present the data.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations